Histologic profile and CD44 expression in breast cancer tissue of balur nano divine kretek volunteers - Dody Novrial; A’liyatur Rosyidah; Saraswati Saraswati; Subagjo Subagjo; Sarjadi Sarjadi (The East Java Biological Society, 2016)
Breast cancer is the most common cancer in woman. Accumulation of free radical in the body is one of cancer risk fac-tors. Since 2009, Research Institute for Free Radicals Shedding Malang has been developing balur nano divine kretek method, combination of balur and divine tobacco smoke to decay free radicals. It has been tested on volunteers with cancer, including breast cancer. This study aimed to assess the effect of balur nano divine kretek method to breast can-cer tissue and CD44 expression. The results showed that 66.67% tumor samples suffered extensive damage (grade 3) and high CD44 expression. The high expression of CD44 in most of the samples may indicate better prognosis. The augmentation for the effectiveness consistency of balur nano divine kretek should be continuously conducted with greater samples and more complete molecular markers such as CD24 and ALDH.